Mechanisms underlying rapid experience-dependent plasticity in the human visual cortex - Boroojerdi, Babak (The National Academy of Sciences, 2001)
Visual deprivation induces a rapid increase in visual cortex excitability that may result in better consolidation of spatial memory in animals and in lower visual recognition thresholds in humans. γ-Aminobutyric acid (GABA)ergic, N-methyl-d-aspartate (NMDA), and cholinergic receptors are thought to be involved in visual cortex plasticity in animal studies. Here, we used a pharmacological approach and found that lorazepam (which enhances GABA(A) receptor function by acting as a positive allosteric modulator), dextrometorphan (NMDA receptor antagonist), and scopolamine (muscarinic receptor antagonist) blocked rapid plastic changes associated with light deprivation. These findings suggest the involvement of GABA, NMDA, and cholinergic receptors in rapid experience-dependent plasticity in the human visual cortex.